2020
DOI: 10.1038/s41598-020-67749-1
|View full text |Cite
|
Sign up to set email alerts
|

A candidate multi-epitope vaccine against SARS-CoV-2

Abstract: In the past two decades, 7 coronaviruses have infected the human population, with two major outbreaks caused by SARS-CoV and MERS-CoV in the year 2002 and 2012, respectively. Currently, the entire world is facing a pandemic of another coronavirus, SARS-CoV-2, with a high fatality rate. The spike glycoprotein of SARS-CoV-2 mediates entry of virus into the host cell and is one of the most important antigenic determinants, making it a potential candidate for a vaccine. In this study, we have computationally desig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(206 citation statements)
references
References 129 publications
13
192
0
1
Order By: Relevance
“…Recently, several groups have reported construction of multi-epitope vaccine against SARS-CoV-2 through immunoinformatics approach using various viral proteins. For instance, spike glycoprotein of SARS-CoV-2 has been evaluated extensively to design different multi-epitope vaccines (Abraham Peele et al., 2020 ; Kar et al., 2020 , Samad et al., 2020 ). Additionally, spike protein has also been used in combination of epitopes from other viral proteins including nucleocapsid and membrane (Kalita et al., 2020 ), protein 8 (Nsp8) and 3 C-like proteinase (Ahmad et al., 2020 ), main protease, Nsp12 (polymerase) and Nsp13 (helicase) (Rehman et al., 2020 ) for construction of peptide-based vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups have reported construction of multi-epitope vaccine against SARS-CoV-2 through immunoinformatics approach using various viral proteins. For instance, spike glycoprotein of SARS-CoV-2 has been evaluated extensively to design different multi-epitope vaccines (Abraham Peele et al., 2020 ; Kar et al., 2020 , Samad et al., 2020 ). Additionally, spike protein has also been used in combination of epitopes from other viral proteins including nucleocapsid and membrane (Kalita et al., 2020 ), protein 8 (Nsp8) and 3 C-like proteinase (Ahmad et al., 2020 ), main protease, Nsp12 (polymerase) and Nsp13 (helicase) (Rehman et al., 2020 ) for construction of peptide-based vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations in the spike protein and RBD of SARS-CoV and MERS-CoV are believed to have played a significant evolutionary factor in the transmission of the virus from bats to humans and influenced binding potentials to host receptors [23][24][25]. Mutations increasing affinity to virus receptors are ubiquitous [26,27], and exploring how mutations in the RBD region of SARS-CoV-2 impact the spike protein would aid in the design of better inhibitors and potential vaccines [28].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it is expected that both intracellular and extracellular virus reservoirs are attacked to help rapid viral clearance, even in the absence of neutralizing antibodies. (62,63) We demonstrated that individuals' anti-SARS-CoV-2 T cell responses reactive to the PolyPEPI-SCoV-2 peptide set are HLA genotype-dependent. Specifically, multiple autologous HLA binding epitopes (PEPIs) determine antigen-specific CD8 + T cell responses with 84% accuracy.…”
Section: Discussionmentioning
confidence: 92%